2017
DOI: 10.3390/agronomy7040068
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Precision Mobile Drip Irrigation in the Texas High Plains Region

Abstract: Mobile drip irrigation (MDI) technology adapts driplines to the drop hoses of moving sprinkler systems to apply water as the drip lines are pulled across the field. There is interest in this technology among farmers in the Texas High Plains region to help sustain irrigated agriculture. However, information on the performance of this system and its benefits relative to common sprinkler application technologies in the region are limited. A two-year study was conducted in 2015 and 2016 to compare grain yields, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The 63 rd , and 50 th DAPs however, belong to vegetative growth stage. Here, the important variables selected by machine learning algorithm were all before blister stage, shortly after pollination when the maize kernels are just forming [ 60 ]. It is unknown if the importance of this late vegetative to early reproductive period was unique to this studies germplasm and environments, or if it has greater general applicability.…”
Section: Discussionmentioning
confidence: 99%
“…The 63 rd , and 50 th DAPs however, belong to vegetative growth stage. Here, the important variables selected by machine learning algorithm were all before blister stage, shortly after pollination when the maize kernels are just forming [ 60 ]. It is unknown if the importance of this late vegetative to early reproductive period was unique to this studies germplasm and environments, or if it has greater general applicability.…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 corn study with irrigation capacity treatments limited to 3.1 mm d -1 resulted in MDI having 35% lower soil water evaporation and significantly greater end-of season soil water compared to LESA (Kisekka et al, 2017). In a similar 2015-2016 corn study, MDI resulted in greater WUE than either LESA or LEPA in the dryer 2016 growing season (O'Shaughnessy and Colaizzi, 2017). Comparisons of LEPA to MDI at Halfway, Texas, showed no consistent differences in yield between the two methods for grain sorghum or cotton (table 4).…”
Section: Other Irrigation Researchmentioning
confidence: 99%
“…An MDI system was recently commercialized as a retrofit to existing center pivot and lateral move irrigation systems. The MDI system applies water through specially designed surface driplines that are pulled through fields by the irrigation machine (Kisekka et al, 2017;O'Shaughnessy and Colaizzi, 2017). Similar to the LEPA method, which applies water on the soil surface between crop rows, MDI reduces water losses due to spray evaporation, evaporation from a wetted canopy, and wind drift resulting in increased efficiency.…”
Section: Gravitymentioning
confidence: 99%
“…One advantage MDI may have over LEPA or LESA is its potential use on topography of greater slope without using furrow dikes, due to its extended wetting pattern. Studies in Texas and Kansas have shown that MDI results in improved CWP compared with LEPA or LESA for corn in years with average to below average precipitation, but not for years with above average precipitation (Kisekka et al, 2017;O'Shaughnessy and Colaizzi, 2017). Additional studies are clearly needed to test MDI vs. LEPA or LESA for cotton, particularly in drought conditions.…”
Section: Gravitymentioning
confidence: 99%